Basic Issues of Management in the Field of Public Security - Wiśniewski, Wojciech (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
The issue of management in the area of public security is a subject under intensive research due to its importance for managing the security of the state. In a high standard manner, this problem was addressed in Poland in an organized way in the beginning of the 20th century. The management of public security is exercised by the authorities and public administration. The authorities set up the legal basis and introduce organizational solutions. Public administration is responsible for the full and effective organization of management in this type of safety. In the present paper, the Author presents basic management problems in the area of public security using several theoretical methods.